Replacement of xylene with extra virgin coconut oil in the clearing step of the histological routine - Abreu , Brenda Oliveira de; Messias , Inalda Maria de Oliveira; Araújo , Rosane Jamille de Oliveira; Florêncio , Mônica Simões; Filho , João Ferreira da Silva; Messias , Júlio Brando (Seven Editora, 2023)
Xylol is a compound used in histological processing, and in the clearing step, and is a harmful solvent for public health and the environment. The objective of this study was to present an alternative methodology to the use of xylene, in the diaphanization stage of the histological routine using extra virgin coconut oil. Fragments of the ear, cerebellum, and tongue of Rattus norvegicus divided into five groups were used. The control group was cleared with xylene, a treated group I with xylene and 30% coconut oil, treated II with xylene and 50% coconut oil, treated III with xylene and 70% coconut oil and treated IV only with coconut oil. Slides from all groups and tissues were stained with Harris Hematoxylin and Eosin, cerebellum slides were also stained with Phosphotungstic Hematoxylin and Eosin, tongue slides by Gomori's Trichrome method, and ear slides by Orcein with Harris Hematoxylin. The evaluated tissues did not show differences between the groups in the process of clearing, blocking, and staining, the clearing action of the oil maintained the morphology of the tissues and did not interfere with the staining. We can conclude that coconut oil is a promising substitute for the use of xylene in the clearing step, being a safer and low-cost alternative, not compromising the morphology of the tissues and without interfering with the different stains used, in addition to minimizing the risks to public and environmental health. DOI:https://doi.org/ 10.56238/devopinterscie-133